Effect Of Spacing And Plant Density On Yield Performance Of Determinate Soybean Variety Tarkari Bhatmas-1 Under Mid Hill Condition - Shrestha, Renuka; Das, Soni; Neupane, Reshama (Agronomy Journal of Nepal, 2021)
Field experiments consisting nine spacing: three row to row (inter row: 43 cm, 50 cm and 60 cm) and three plant to plant (intra row: 10 cm, 15 cm and 20 cm) with plant population ranging from 8-23/m2 were evaluated in randomized complete block design (RCBD) with four replications from 2014-2016 in Agronomy Farm, Lalitpur, Nepal. Seeds were sown on 29 May 2014, 31 May 2015 and 26 May 2016. Chemical fertilizers 30 N:60 P2O5:30 K2O kg/ha were applied as basal dose. Combined analysis showed significant variation in final plant stand, grain yield and numbers of pod/plant amongst different inter row and intra row spacing, while other parameters were not statistically significant. Grain yields were at par at inter row spacing of 43-60 cm and intra row spacing of 10-15 cm (11-23 plants/m2). Grain yield was reduced by 7-21% when intra row spacing was more than 10 cm, with the greatest reduction in wider intra row spacing of 20 cm. Greater number of pods/plant in wide spacing indicated the ability of soybean to compensate for low plant population to some extent. Plant grew taller in narrow intra row spacing than wider spacing, but seed size was not affected by spacing. Wider intra row spacing was found to have greater influence in term of grain yield than inter row spacing in case of early maturing determinate variety under Khumaltar condition. Inter row spacing of 43-60 cm and intra row spacing of 10-15 cm were found to be optimum for early maturing determinate soybean under Kathmandu valley and similar environments.